Wind Power Plants Fundamentals, Design, Construction and Operation - Gasch, Robert; Twele, Jochen; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
Wind power plants teaches the physical foundations of usage of Wind Power. It includes the areas like Construction of Wind Power Plants, Design, Development of Production Series, Control, and discusses the dynamic forces acting on the systems as well as the power conversion and its connection to the distribution system. The book is written for graduate students, practitioners and inquisitive readers of any kind. It is based on lectures held at several universities. Its German version it already is the standard text book for courses on Wind Energy Engineering but serves also as reference for practising engineers.
Questionnaire -- Introduction -- Historical development of windmills -- Design and components -- The wind blade geometry -- Calculation of performance characteristics -- Scaling wind turbines and rules of similarity -- Structural dynamics -- Guidelines and analysis procedures -- Wind pump systems -- Electricity generation -- Supervisory and control systems -- Concepts of electricity generation -- Operation at the interconnected grid -- Planning, operation and economics -- Offshore windfarms.
Keywords: Engineering; Hydraulic engineering; Mechanical engineering; Ocean engineering; Renewable energy sources; Engineering; Renewable and Green Energy; Offshore Engineering; Mechanical Engineering; Engineering Fluid Dynamics